2018
DOI: 10.1111/1365-2745.12939
|View full text |Cite
|
Sign up to set email alerts
|

Independent effects of host and environment on the diversity of wood‐inhabiting fungi

Abstract: Dead wood is a habitat for numerous fungal species, many of which are important agents of decomposition. Previous studies suggested that wood‐inhabiting fungal communities are affected by climate, availability of dead wood in the surrounding landscape and characteristics of the colonized dead‐wood object (e.g. host tree species). These findings indicate that different filters structure fungal communities at different scales, but how these factors individually drive fungal fruiting diversity on dead‐wood object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
99
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 94 publications
(110 citation statements)
references
References 84 publications
7
99
0
4
Order By: Relevance
“…However, we found that although the amount of dead wood was high on our study plots in early stages of forest succession (Supporting Information Figure S11), this was not reflected in the number of species of wood-decaying (saproxylic) fungi. This is consistent with the more detailed analyses of Krah et al (2018), which show that the mere amount of dead wood is a relatively poor predictor of the number of these fungal species. The number of fungal species might be driven more strongly by the host tree species, host size, dieback history, and canopy openness than by the amount and heterogeneity of dead wood (Abrego & Salcedo, 2013;Heilmann-Clausen et al, 2015;Krah et al, 2018).…”
Section: Ecology Of Taxasupporting
confidence: 89%
See 1 more Smart Citation
“…However, we found that although the amount of dead wood was high on our study plots in early stages of forest succession (Supporting Information Figure S11), this was not reflected in the number of species of wood-decaying (saproxylic) fungi. This is consistent with the more detailed analyses of Krah et al (2018), which show that the mere amount of dead wood is a relatively poor predictor of the number of these fungal species. The number of fungal species might be driven more strongly by the host tree species, host size, dieback history, and canopy openness than by the amount and heterogeneity of dead wood (Abrego & Salcedo, 2013;Heilmann-Clausen et al, 2015;Krah et al, 2018).…”
Section: Ecology Of Taxasupporting
confidence: 89%
“…(), which show that the mere amount of dead wood is a relatively poor predictor of the number of these fungal species. The number of fungal species might be driven more strongly by the host tree species, host size, dieback history, and canopy openness than by the amount and heterogeneity of dead wood (Abrego & Salcedo, ; Heilmann‐Clausen et al., ; Krah et al., ).…”
Section: Discussionmentioning
confidence: 97%
“…Fungi can be strongly affected by microsite conditions, as shown by some studies (e.g., Krah et al, , Pouska, Macek, & Zíbarová, ), and others which are still hypothesized to affect fungi. While we cannot cover all microsite conditions or their measurement methodology here, it is important to be aware of their effect and, where possible, measure those relevant to study questions.…”
Section: Standardized Environmental Measurementsmentioning
confidence: 91%
“…Fungi can be strongly affected by microsite conditions, as shown by some studies (e.g., Krah et al, 2018, Pouska, Macek, & Zíbarová, 2017, and others which are still hypothesized to affect fungi.…”
Section: Microsite Conditionsmentioning
confidence: 93%
“…Bisherige Studien konnten allerdings die Effekte von Totholzmenge und Mikroklima auf die Holzpilzdiversität nicht vollständig aufklären, da beide Einflussfaktoren in Wäldern miteinander stark korreliert sind. Ein experimenteller Ansatz im Nationalpark hat gezeigt, dass das Mikroklima, unabhängig von der Totholzmenge, eine wichtige Steuergröße für die Zusammensetzung von Artengemeinschaften ist . Des Weiteren wurde in zwei unabhängigen Experimenten belegt, dass der bestimmende Faktor der Pilzartengemeinschaften die Baumart ist .…”
Section: Die Wichtigsten Steuergrößen Der Holzpilzdiversitätunclassified